Expresión (a⇒b)∧(b⇒a)
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
a⇒b=b∨¬ab⇒a=a∨¬b(a⇒b)∧(b⇒a)=(a∧b)∨(¬a∧¬b)
(a∧b)∨(¬a∧¬b)
Tabla de verdad
+---+---+--------+
| a | b | result |
+===+===+========+
| 0 | 0 | 1 |
+---+---+--------+
| 0 | 1 | 0 |
+---+---+--------+
| 1 | 0 | 0 |
+---+---+--------+
| 1 | 1 | 1 |
+---+---+--------+
(a∧b)∨(¬a∧¬b)
(a∨¬a)∧(a∨¬b)∧(b∨¬a)∧(b∨¬b)
(a∨(¬a))∧(a∨(¬b))∧(b∨(¬a))∧(b∨(¬b))
(a∨¬b)∧(b∨¬a)
Ya está reducido a FND
(a∧b)∨(¬a∧¬b)